Changes in macronutrient content in sludge as affected by sources and seasons - CHOUDHARY, MAHIPAL; DATTA, SIBA PRASAD; MEENA, MAHESH CHAND; DWIVEDI, B S; GOLUI, DEBASIS; SHARMA, VINOD KUMAR; TRIVEDI, VIVEK KUMAR; PATTANAYAK, ARUNAVA; PATEL, K C (The Indian Journal of Agricultural Sciences, 2021)
An attempt has been made in assessing variability of macronutrient content in sludge as affected by sources and seasons at Indian Agricultural Research Institute, New Delhi. For this purpose, sludge samples were collected from eight different sewage treatment plants (STPs) located in and around Delhi (CP: Coronation Pillar, DG: Delhi Gate Nalla, KSP: Keshopur, NIL: Narella, NLT: Nilothi, OKH: Okhla, PPK: Pappankallan and RTL: Rithala) in 2018-19. Results indicated that sludge samples collected from different sources were acidic in nature and varied from 6.34 to 6.65 with mean of 6.44, and electrical conductivity of sludge ranged from 2.95 to 5.74 dS/m with mean of 4.17 dS/m. Sludge generated at different (STPs) of Delhi were rich in total carbon (TC) (10.5-35.1%) and macronutrients, viz. nitrogen (N) (1.21-2.64%) and phosphorus (P) (0.95-1.84%); but the potassium (K) content (0.16-0.32%) was much lower. The corresponding mean values of TC, N, P and K in sludge samples across the sources and seasons were 20.4, 1.98, 1.35 and 0.24%, respectively. Seasonal occurrence pattern of macronutrient, i.e. N, P, and K were higher in sludge collected during summer followed by winter and rainy season. Sludge can be a potential source of plant nutrients, particularly in the face of rise in the price of NPK fertilizers.